The role of information technology applications represented by electronic payment and distribution services in improving the quality of banking performance: a field study on a sample of Iraqi banks - Thamer, Hussein; Mardan, Zaid Ayd; hassan, Ezzaddin; zuhair, Qasim; obaid, Raheem (The journal of contemporary issues in business and government, 2023)
This study aimed to identify the concept of information technology in general and to indicate the extent of its impact on improving banking performance and the quality of banking service by saving time and effort and reducing the cost of completing the work by obtaining the required outputs from the various inputs. The questionnaire was used as a method for collecting data for the opinions of a sample. Of the employees of the surveyed banks, by distributing (87) a questionnaire to a sample of customers and employees of Al-Rafidain and Al-Rashid Bank operating in the province of Babylon, the data were analyzed using the statistical program (SPSS v.25.). The research has reached a set of conclusions, the most important of which is that the use of technology in the banking business has become an urgent necessity, which requires equipment, development, and training to raise the level of services provided » There is also a statistically significant relationship between the use of information technology (electronic payment methods and distribution channels electronic) and improve banking performance. The study recommends that it is necessary to pay attention to information technology and its continuous development for its effective contribution to the success of banking services. This study is considered important for the management of banks and decision- makers by shedding light on information technology and showing its impact on enhancing banking service, which in turn is reflected in increasing customer loyalty towards the bank.